CO Digestion for Biogas Production from Tapioca Industrial Wastewater and Septage - Agus Hadiyarto; Danny Soetrisnanto; Asep Muhammad Samsudin; Prinanda De Aqila Asri; Said Abdillah (ASEAN Journal of Chemical Engineering, 2018)
In this study, a combination of substrate rich carbon with substrate rich nitrogen was carried out. The experiments were conducted in batches process by varying the C/N ratio and types of anaerobic microbial sludge of the cow rumen, anaerobic microbial sludgefrom wastewater treatment plant (WWTP) of septage and anaerobic sludge from WWTP of tapioca industry. Practically in the range of C/N ratio 20-30 didn’t give a significant effect on the biogas production.The C/N 30 ratio provides the most biogas production rate, while the microbe derived from the cow rumen gives the most biogas production rate.Adaptation phase occurred up to 11th days, growth phase occurred lasted until day 24st, stationary phase occurred in the range of day 24th-31st and death phase occurred after day 31st. Biogas yield (by cow rumen) is 1,127 liters per kg of COD removed or 161 liters per kg of COD per day.